Morphologische Reanalyse: Verbbildung durch -en/-igen im Alt- und Mittelhochdeutschen - Kuroda, Susumu (Studia Germanica Posnaniensia, 2018)
The German suffixes -en/-igen serve to build a verb out of a noun or an adjective as in Arbeit ‚work’ – arbeiten ‚to work’, reif ‚ripe’ – reifen ‚to ripen’, Pein ‚torment’ – peinigen ‚to torment’, rein ‚pure’ – reinigen ‚to clean’. In many cases, however, this is only possible with a preverb, as langsam ‚slow’ – *langsamen – verlangsamen ‚to slow down’, Brille ‚spectacle’ – *brillen – bebrillen ‚to bespectacle’. By using the notion of unification developed in Construction Morphology, verbs such as verlangsamen or bebrillen above can be accounted for as a direct derivation from a noun or an adjective if one assumes the existence of a ‚unified’ word formation pattern [P-[[N/A]-en]V] as a fusion of [[N/A]-en]V and P-[V]. Since the Middle High German period, the use of -igen as a functionally equivalent to -en can be seen increasingly. This suffix is also characterizable as a unification of two conversion patterns, one with the adjectivizing suffix -ig and the other with the verbalizing -en. This process should be called ‚morphological reanalysis’ for the adjectivizing function of -ig is invalidated here. The development of ‚unified’ word-formation-patterns [P-[[N/A]-en]V] as well as the pattern with -igen can be ascertained first in Middle High German.